2018
DOI: 10.1038/s41467-018-05734-z
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry regimes for circular photocurrents in monolayer MoSe2

Abstract: In monolayer transition metal dichalcogenides helicity-dependent charge and spin photocurrents can emerge, even without applying any electrical bias, due to circular photogalvanic and photon drag effects. Exploiting such circular photocurrents (CPCs) in devices, however, requires better understanding of their behavior and physical origin. Here, we present symmetry, spectral, and electrical characteristics of CPC from excitonic interband transitions in a MoSe2 monolayer. The dependence on bias and gate voltages… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 26 publications
2
78
0
Order By: Relevance
“…Bilayer graphene (BLG) with the band gap and conductivity tunable by a gate electric field is in the focus of stateof-the-art carbon electronics and optoelectronics [1][2][3][4][5][6][7][8][9][10]. Of particular interest are second-order nonlinear phenomena such as second harmonic generation, photogalvanic, photon drag, plasmonic, photothermoelectric, and ratchet effects, where the ac electric field of the laser radiation drives an ac electric current at the double frequency or a dc electric current [11][12][13][14][15][16][17][18][19]. In bilayer graphene so far only bulk mechanisms of the current generation were considered [20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Bilayer graphene (BLG) with the band gap and conductivity tunable by a gate electric field is in the focus of stateof-the-art carbon electronics and optoelectronics [1][2][3][4][5][6][7][8][9][10]. Of particular interest are second-order nonlinear phenomena such as second harmonic generation, photogalvanic, photon drag, plasmonic, photothermoelectric, and ratchet effects, where the ac electric field of the laser radiation drives an ac electric current at the double frequency or a dc electric current [11][12][13][14][15][16][17][18][19]. In bilayer graphene so far only bulk mechanisms of the current generation were considered [20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Photogalvanic effects have been studied extensively for 2D electron gases in III-V semiconductors [89]. Furthermore, they have been applied both experimentally and theoretically to van der Waals materials, including 3D topological insulators [58,59,62,[93][94][95][96][97][98][99], 2D TMDs [17,18,100], WS 2 nanotubes [101], polar van der Waals materials [102,103], and layered Weyl semimetals [104][105][106][107]. Photogalvanic currents form an effective toolbox to explore fundamental optoelectronic symmetries.…”
Section: General Symmetry Considerations For Light-driven Currentsmentioning
confidence: 99%
“…It was recently shown that when a monolayer TMD (1L-TMD) is illuminated at an oblique angle with respect to the crystal plane, a helicity-dependent photocurrent (circular photocurrent, CPC) emerges. This effect has been attributed to circular photogalvanic (CPGE) and photon drag (CPDE) effects [10][11][12] and opens exciting possibilities for the realization of 2D self-powered optoelectronic and opto-spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the emergence of CPGE requires a low crystal symmetry not compatible with the D 3h symmetry found in pristine 1L-TMDs. Therefore, it requires an external agentsuch as mechanical strain or a strong external electric fieldto reduce the crystal symmetry to, at most, a single mirror-plane symmetry 11 . One possible agent that can cause this symmetry breaking is the strong electric field that emerges in Schottky contacts to 1L-TMDs 13 when an external bias is applied.…”
Section: Introductionmentioning
confidence: 99%